A Cost-Effective, Adjustable, Dynamic Subcortical Stimulation Device – Technical Note. (2nd October 2022) - Silverstein, Justin W.; Greisman, Jacob D.; Dadario, Nicholas B.; Park, Jung; D'Amico, Randy S.
ABSTRACT: Brain mapping and neuromonitoring remain the gold standard for identifying and preserving functional neuroanatomic regions during safe, maximal brain tumor resection. Subcortical stimulation (SCS) can identify white matter tracts and approximate their distance from the leading edge of an advancing resection cavity. Dynamic (continuous) devices permitting simultaneous suction and stimulation have recently emerged as time-efficient alternatives to traditional static (discontinuous) techniques. However, the high cost, fixed cap size, and fixed tube diameter of commercially available suction devices preclude universal adoption. Our objective is to modify available suction devices into monopolar probes for subcortical stimulation mapping. We describe our technique using a novel, cost-effective, dynamic SCS technique as part of our established neuromonitoring protocol. We electrified and insulated a conventional variable suction device using an alligator clip and red rubber catheter, respectively. We adjusted the catheter's length to expose metal on both sides, effectively converting the suction device into a monopolar stimulation probe capable of cortical and subcortical monopolar stimulation that does not differ from commercially available discontinuous or continuous devices. We fashioned a dynamic SCS suction probe using inexpensive materials compatible with all suction styles and sizes. Qualitative and quantitative analysis in future prospective case series is needed to assess efficacy and utility.